La realidad virtual como estrategia metodológica en el desarrollo de destrezas para niños de Educación Inicial - Mena Pinzón, Fernando Fabián (2024)
The Educational Units of the city of Ambato are characterized by providing quality education from the initial cycles despite different factors that make it difficult for students to learn correctly. For this reason, it is essential to implement new technologies that help teachers teach their skills. classes effectively. The present project arises from the identification of the problem that teachers have regarding the lack of permits from the authorities of the institutions to be able to take children outside the educational unit, for this reason the implementation of the use of virtual reality in the process of skill development of early childhood children. Through bibliographic and field research, information has been collected to verify the usefulness of this research project, taking as valid points of view, bibliographic documentation that is related to the topic developed, in addition, the points of view of both professionals in the field. field of virtual reality, as well as the current knowledge and strategies used by teachers. The results obtained show that the use of virtual reality in the educational field is very useful for the development of skills in children of initial cycles, since it provides the opportunity to learn in a personalized way about the elements of the environment, in this way The child no longer only observes flat figures, but can observe objects that provide spatial information attached to reality